2018
DOI: 10.1039/c8ra06217j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, surface activities, and aggregation behavior of phenyl-containing carboxybetaine surfactants

Abstract: A novel series of carboxybetaine surfactants were synthesized for the first time and their physicochemical properties were systematically investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The 1 H and 13 C NMR spectra of products were shown in the Supporting Information (Figures S1–S4). The synthesis of 2-(alkoxy)-1,3-dimethylbenzene (C n OB) and 5-(chloromethy)-2-(alkoxy)-1,3-dimethylbenzene (C n OBMCl) with n = 12, 14, and 16 was reported in our previous article …”
Section: Experimental Methodsmentioning
confidence: 99%
“…The 1 H and 13 C NMR spectra of products were shown in the Supporting Information (Figures S1–S4). The synthesis of 2-(alkoxy)-1,3-dimethylbenzene (C n OB) and 5-(chloromethy)-2-(alkoxy)-1,3-dimethylbenzene (C n OBMCl) with n = 12, 14, and 16 was reported in our previous article …”
Section: Experimental Methodsmentioning
confidence: 99%
“…The ESI-HRMS spectrum was determined by a Bruker FT-ICR-MS spectrometer. The alkylbetaine surfactants (ASB 12 and ACB 12 ) were reported in several preceding articles , and synthesized for comparison, while the novel phenyl-containing betaine surfactants with a hydrocarbon chain length of 10 (BSB 10 and BCB 10 ) were prepared according to our previous works. , The synthesis routes and procedures of four betaine surfactants are shown in the Supporting Information along with the 1 H and 13 C NMR spectra of products . Their molecule structural data were given as follows.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It is well known that the chemical structures of betaine surfactants are a crucial part in determining their physicochemical properties and even their application fields. To obtain comprehensive understanding of betaine surfactants, many studies have been carried out to synthesize novel kinds of betaine surfactants. Most studies have concentrated on investigating the effect of hydrophobic moieties modifications, the hydrocarbon chain length, and the types of hydrophilic headgroups , on physicochemical properties. For example, Kelleppan et al synthesized five long-chain amidopropyl betaines with C18 tailgroups and found that different degrees of unsaturation and branching significantly affect aggregation structures.…”
Section: Introductionmentioning
confidence: 99%
“…A higher magnitude of DG q ads is observed as compared to DG q m values, showing that adsorption process favorably occurs until all the air/solution interface is occupied, and then surfactants molecules begin to aggregate and form micelles in the bulk solution. 58,59 DG q m and DG q ads become more negative with increasing alkyl chain length or solution temperature. This may be due to the increased hydrophobicity of ILs, which can destroy the structure of water and increase free energy of the system, and improve the propensity of ILs molecules to migrate to the interface.…”
Section: Thermodynamics Of Micellizationmentioning
confidence: 97%
“…Thus the values of DG q m and DG q ads are more negative. 59 Rising temperature can cause the decrease of hydration around hydrophilic groups, which results in the increase of the system energy, improves protably to adsorption in the interface and formation of micelles in order to decrease energy of the surfactant system. 16,37,38 60,61 The hydrophobic effect is related to the water removal from the nonpolar surface in order to diminish the extent of less favorable hydrophobic hydration in comparison to clustered water in the bulk.…”
Section: Thermodynamics Of Micellizationmentioning
confidence: 99%